1981
DOI: 10.1007/bf00584574
|View full text |Cite
|
Sign up to set email alerts
|

Dietary obesity in adult and weanling rats following removal of interscapular brown adipose tissue

Abstract: In order to investigate the role of brown adipose tissue (BAT) in diet-induced thermogenesis (DIT), a selection of palatable, energy-dense foods (Cafeteria diet) was used to increase the energy intakes of adult and weanling male rats, from some of which interscapular BAT (IBAT) had been surgically excised. Removal of IBAT had no effect upon energy intakes of the cafeteria-fed rats, nor of controls fed a pelleted stock diet. The rate of weight gain of intact controls was similar for the two diets, but adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…The argument is as follows (Figure 2): 1) individuals with low BAT levels are prone to excess accumulation of white adipose tissue and weight gain (Hansen and Kristiansen, 2006); 2) visceral adiposity and obesity are strongly associated with the risk for several major age-related diseases including type 2 diabetes, cardiovascular disease, stroke and some cancers (Phillips and Prins, 2008); 3) dietary energy restriction, which increases levels of BAT, protects against diabetes, cardiovascular disease, stroke, cancers (Varady and Hellerstein, 2007; Stranahan and Mattson, 2008) and possibly neurodegenerative disorders such as Alzheimer's disease (Maalouf et al, 2009); and 4) BAT removal promotes white adipose tissue growth and weight gain (Stephens et al, 1981; Stern et al, 1984). …”
Section: Dietary Energy Intake Bat and Agingmentioning
confidence: 99%
“…The argument is as follows (Figure 2): 1) individuals with low BAT levels are prone to excess accumulation of white adipose tissue and weight gain (Hansen and Kristiansen, 2006); 2) visceral adiposity and obesity are strongly associated with the risk for several major age-related diseases including type 2 diabetes, cardiovascular disease, stroke and some cancers (Phillips and Prins, 2008); 3) dietary energy restriction, which increases levels of BAT, protects against diabetes, cardiovascular disease, stroke, cancers (Varady and Hellerstein, 2007; Stranahan and Mattson, 2008) and possibly neurodegenerative disorders such as Alzheimer's disease (Maalouf et al, 2009); and 4) BAT removal promotes white adipose tissue growth and weight gain (Stephens et al, 1981; Stern et al, 1984). …”
Section: Dietary Energy Intake Bat and Agingmentioning
confidence: 99%
“…Sham‐operated or experimental groups had lower FI within the first 24 hours following surgery, likely because of the stress of the procedure and effects of anesthesia. The observed FI was similar among sham‐operated and experimental groups fed chow diets in mice and higher in HFD‐fed groups . C57BL/6J mice with WAT transplanted had lower FI compared with the control group .…”
Section: Resultsmentioning
confidence: 68%
“…Both Lister Hooded rats with removed BAT and Long Evans rats with WAT lipectomized or transplanted had increased BW. Therefore, changes in BW in most rat studies in the long term (or at termination) were not significantly different compared with baseline weight, with the exception of a few studies .…”
Section: Resultsmentioning
confidence: 97%
“…Thus, in both cases one would expect the BAT func tion to be impaired. Such impairment has been shown to lead to increased body weight in both young and adult rats [5], presumably by preventing extra calories from being con verted into heat. Since overfed infant rats have elevated plasma cholesterol levels [ 17] and decreased HMGR activity, we expected similar changes in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, they may also cause obesity [5] and as a result of that affect the metabolism of cholesterol [6]. It has also been reported that drugs that lower blood pressure (inhibitors of the sympathetic ner vous system) frequently raise the level of plasma lipids [7], For the above reasons we administered some blood-pressure-lowering drugs to in fant and weaned rats and examined the re sponses of plasma lipids and enzymes of cho lesterol metabolism, assuming that inhibi tion of BAT heat production would have the same effect as removal of the tissue [5], i.e., a tendency towards increased weight gain and thus elevated plasma lipid levels. This as sumption was not borne out by the experi ments reported below.…”
mentioning
confidence: 99%